ANALYSIS OF THE EFFECT OF DIGITAL CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY THROUGH EMOTIONAL MARKETING AND CUSTOMER SATISFACTION FOR INDIHOME CUSTOMERS - Yessi Claudia Sianipar; Syafrizal Helmi Situmorang; Rulianda Purnomo Wibowo (CV. Radja Publika, 2023)
Some of the conclusions obtained from this research are as follows following: Digital customer experiencesignificantly influence customer satisfaction. This shows that the greater the digital customer experience value that can be felt by customers, the customer satisfaction will increase. Digital customer experiencesignificantly influence emotional marketing. In this study, the relationship between these two variables is the closest of all variables because it has the highest path coefficient and t values. This shows that the greater the value of the digital customer experience, the greater the emotional marketing that customers can feel. emotional marketingsignificantly influence customer satisfaction. This shows that the greater the value of emotional marketing that can be felt by customers, the customer satisfaction will increase. emotional marketingsignificantly influence customer loyalty. This means that the greater the value of emotional marketing that can be felt by customers, the customer loyalty will increase. Customer satisfactionsignificantly influence customer loyalty. This shows that the greater the value of customer satisfaction, the greater customer loyalty will be. Digital customer experiencesignificantly influence customer loyalty through customer satisfaction. Digital customer experiencesignificantly influence customer loyalty through emotional marketing. emotional marketingsignificantly influence customer loyalty through customer satisfaction. Digital customer experiencesignificantly influence customer satisfaction through emotional marketing. Digital customer experiencesignificantly influence customer loyalty through emotional marketing and customer satisfaction.